2022
DOI: 10.1111/tpj.15685
|View full text |Cite
|
Sign up to set email alerts
|

KIN3 impacts arbuscular mycorrhizal symbiosis and promotes fungal colonisation in Medicago truncatula

Abstract: Arbuscular mycorrhizal fungi help their host plant in the acquisition of nutrients, and this association is itself impacted by soil nutrient levels. High phosphorus levels inhibit the symbiosis, whereas high nitrogen levels enhance it. The genetic mechanisms regulating the symbiosis in response to soil nutrients are poorly understood. Here, we characterised the symbiotic phenotypes in four Medicago truncatula Tnt1-insertion mutants affected in arbuscular mycorrhizal colonisation. We located their Tnt1 insertio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 88 publications
(129 reference statements)
0
11
0
Order By: Relevance
“…S3, E and F ). In sum, KIN3 is required for the development of arbuscules in L. japonicus , similar to MtKIN3 and OsARK1 ( Bravo et al 2016 ; Roth et al 2018 ; Irving et al 2022 ).…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…S3, E and F ). In sum, KIN3 is required for the development of arbuscules in L. japonicus , similar to MtKIN3 and OsARK1 ( Bravo et al 2016 ; Roth et al 2018 ; Irving et al 2022 ).…”
Section: Resultsmentioning
confidence: 71%
“…2 and Supplemental Fig. S3 ), indicating the important role of KIN3 in arbuscule development from the beginning as in M. truncatula , probably in autoregulation of AM fungi in individual cells rather than in the initiation of AM colonization ( Irving et al 2022 ). Osark1 mutants displayed comparable mycorrhization to the wild type at 3 wpi but fewer fungal structures at 6 wpi, supporting the role of OsARK1 in maintaining AM symbiosis ( Roth et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rice, the ARBUSCULAR RECEPTOR-LIKE KINASE 1 and 2, belonging to an undefined receptor-like kinase (RLK) subfamily, govern postarbuscule development and regulation of the AM association (Roth et al, 2018;Montero et al, 2021). In Medicago truncatula, KIN3, an active kinase, accumulates in the endoplasmic reticulum of arbusculated cells, exerting a partial suppression of the host immune response (Irving et al, 2022) and a similar phenotype has been shown for its orthologous protein in Lotus japonicus (Leng et al, 2023). Additionally, the rice kinase gene OsADK1, specifically induced in arbusculated cells, proves indispensable for arbuscular development during AM symbiosis, and the protein accumulates in the nucleus (Guo et al, 2022;Shi et al, 2022).…”
mentioning
confidence: 80%
“…The expression of Kinase 3 (KIN3) is significantly induced during mycorrhizal interactions, and it appears to play an important role that depends on nutrient supply. Recent studies in M. truncatula showed that kin3 mutants display a much lower mycorrhizal infection rate than the wild-type under high-nitrogen conditions, while root colonization under low-nitrogen conditions was not affected, indicating that it plays a role in adjusting the symbiotic response according to soil nitrogen levels (Irving et al, 2022). Interestingly, Shi et al (2022), showed that the expression of the MtKIN3 homolog OsARK1 is regulated by PHRs in rice, further indicating crosstalk between nitrogen and Pi signaling.…”
Section: Regulation Of the Mycorrhizal Symbiosismentioning
confidence: 99%